Hubungan antara riwayat imunisasi dasar lengkap dengan kejadian stunting pada balita - Naswinda Safitri; Lia Lajuna; Juliastuti Juliastuti; Nurlaili Ramli; Yushida Yushida (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is one of the significant global issues hindering human development. The prevalence of stunted children under five is considered a public health concern when it reaches 20% or more. Stunting can be directly affected by infectious diseases, and immunization is an effective method to enhance immunity to prevent communicable diseases (diarrhea and ARI). Therefore, immunization plays an essential role in reducing stunting risks in children by preventing diseases, which can hinder children's growth and development. Purpose: This study aims to investigate the relationship between complete basic immunization history and the incidence of stunting in children under five years old in the working area of Ingin Jaya Public Health Center, Aceh Besar District. Method: This research employed a quantitative method with a descriptive-analytic approach and a cross-sectional study design. The study population consisted of all stunted children under five years old in the working area of Ingin Jaya Public Health Center, totaling 80 individuals. The sampling technique used was multistage cluster random sampling. Results: The findings indicated that a complete basic immunization history (p = 0.022) was significantly associated with stunting among children under five in the study area. Multivariable analysis among the variables studied at Ingin Jaya Public Health Center revealed that a complete basic immunization history was the most dominant factor influencing stunting, with the highest AOR value 0.183 (95% CI: 0.36–0.938). Conclusion: A significant relationship exists between a complete basic immunization history and the incidence of stunting among children under five in the working area of Ingin Jaya Public Health Center, Aceh Besar. Suggestion: It is recommended that the health center collaborate with community leaders to educate the public on the importance of complete basic immunization for children.